Mosquitoes as Potential Bridge Vectors of Malaria Parasites from Non-Human Primates to Humans - Verhulst, Niels O.; Smallegange, Renate C.; Takken, Willem (Frontiers in Physiology, 2012)
Malaria is caused by Plasmodium parasites which are transmitted by anopheline mosquitoes. Until recently, human malaria was considered to be caused by human-specific Plasmodia spp. Studies on the evolution of Plasmodium parasites in non-human primates, however, have indicated that Plasmodium species can switch hosts and may be transferred from non-human primates to humans and vice versa. The requirements for such a cross-species exchange and especially the role of mosquitoes are discussed. One of the most important vectors of human malaria is the mosquito Anopheles gambiae sensu stricto because it is highly anthropophilic and prefers to feed indoors. It is unknown which mosquito species would bite both humans and non-human primates and if so, whether humans and non-human primates share the same Plasmodium vectors. To understand the vector-host interactions that can lead to an increased Plasmodium transmission between species, studies are required that reveal the nature of these interactions. Studying the possible role of non-human primates as a Plasmodium reservoir will contribute to the ongoing efforts of human malaria elimination, and will help to focus on critical areas that should be considered in achieving this goal.